Can foster care ever be justified for weight management?. Issue 3 (13th November 2013) - Williams, G M G; Bredow, Maria; Barton, John; Pryce, Rebekah; Shield, J P H
Abstract : Article nine of the UN Convention of the Rights of the Child states that 'Children must not be separated from their parents unless it is in the best interests of the child.' We describe the impact that placing a child into care can have on long-standing and intractable obesity when this is a component of a child safeguarding strategy. Significant weight loss was documented in a male adolescent following his placement into foster care due to emotional harm and neglect within his birth family. The child's body mass index (BMI) dropped from a peak of 45.6 to 35 over 18 months. We provide brief details of two further similar cases and outcomes. Childhood obesity is often not the sole concern during safeguarding proceedings. Removal from an 'obesogenic' home environment should be considered if failure by the parents/carers to address the obesity is a major cause for concern. It is essential that all other avenues have been explored before removing a child from his birth family. However, in certain circumstances we feel it may be justified.